Pengembangan Tari Kreasi Tari Caping Sekolah Dasar Kecamatan Bangkalan - Andika Surya Nanda (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
Indonesia is known to be rich in culture, considering the diversity of tribes in this archipelagic country. Starting from dances that discuss the story of the struggle of the royal army, romance, to activities that people engage in every day such as farming. Hearing the name, perhaps many people can already guess that this dance tells about farming activities. The word "tani" itself is taken from the word farming. , a noble profession that produces basic materials that can be consumed by people on a daily basis. This dance was created and developed in the Java area, especially Madura in Bangkalan district. The artists in Bangkalan are inspired by agricultural activities which many people engage in as their main livelihood. In every For traditional dances, props are needed that can support the performance. The existence of props can more clearly describe what a dance wants to convey, as is the case with the Tani dance. In order to describe farming activities more realistically, one of the properties needed is caping. Caping is a cone- shaped hat that farmers wear when working. Caping is made from bamboo, with the function of protecting the head while working because it is often exposed to the heat of the sun. It is not surprising that when they see caping, many people associate it with traditional Indonesian society. Caping has a conical shape at the top, forming a mountain and is a symbol of the source of life for living creatures.